Humanization and directed evolution of the selenium-containing scFv phage abzyme. Issue 31 (10th May 2018) - Xu, Yan; Li, Pengju; Nie, Jiaojiao; Zhao, Qi; Guan, Shanshan; Kuai, Ziyu; Qiao, Yongbo; Jiang, Xiaoyu; Li, Ying; Li, Wei; Shi, Yuhua; Kong, Wei; et al.
Abstract : A novel two-step sequential screening strategy used for the improvement of GPX mimics and other abzymes. Abstract : According to the binding site structure and the catalytic mechanism of the native glutathione peroxidase (GPX), three glutathione derivatives, GSH-S-DNP butyl ester (hapten Be), GSH-S-DNP hexyl ester (hapten He) and GSH-S-DNP hexamethylene ester (hapten Hme) were synthesized. By a four-round panning with a human synthetic scFv phage library against three haptens, the enrichment of the scFv phage particles with specific binding activity could be determined. Three phage particles were selected binding to each glutathione derivative, respectively. After a two-step chemical mutation to convert the serine residues of the scFv phage particles into selenocysteine residues, GPX activity could be observed and determined upto 3000 U μmol −1 in the selenium-containing scFv phage abzyme which was isolated by affinity capture against the hapten Be. Also the scFv phage abzymes elicited by different antigens displayed different catalytic activities. After a directed evolution by DNA shuffling to improve the affinity to the hapten Be, a secondary library with GPX activity was created in which the catalytic activity of the selenium-containing scFv phage abzyme could be increased 17%. This study might be helpful for new haptens or antigens design to optimize the abzymes with high binding activities and might also provide a novel scheme for GPX mimic candidates for drug development.